The Use of Video as a Medium to Improve Students’ Ability in Writing Narrative Texts (ELT Forum: Journal of English Language Teaching, 2013)
The aims of this study were to explain and describe how Video was used in teaching writing narrative texts and to find out the result of the teaching writing and learning process after the students were taught by using Video. The subject of this study was VIIIA students of SMP N 24 Semarang. In this research, I used tests and questionnaires to collect the data. I designed an action research that consisted of pretest and two cycles of the treatment. The first meeting was for pretest, the second until the fourth meeting were for treatments using Video in teaching writing in narrative texts and the fifth meeting was for posttest. The result of the study showed that there was an improvement of the students’ writing after the students were taught by using Video. It could be seen from the average of the pretest was 59.8, the first cycle was 68.55, the second cycle was 79.03, and the posttest was 84.82. In conclusion, the use of fairy tail video as a medium worked well in writing class, especially for the VIIIA of SMP N 24 Semarang. The students also said that they were not bored during the teaching and learning process. They felt fun and their motivation to write the narrative texts increased after using Video.  Based on the results above, Video can be an interesting and appropriate medium to teach writing.